Model Collaborative Governance Sistem Peringatan Dini Berbasis Komunitas di Lombok Timur - Lalu Ahmad Murdhani (Jurnal Perlindungan Masyarakat: Bestuur Praesidium, 2025)
This study aims to formulate a collaborative governance model for strengthening community-based early warning systems in East Lombok Regency. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, field observation, focus group discussions, and document analysis involving actors engaged in disaster risk reduction, including local government, the Regional Disaster Management Agency, village governments, local communities, volunteers, academics, private sector actors, civil society organizations, and local media. The data were analyzed thematically through data reduction, theme categorization, data presentation, interpretation, and conclusion drawing. The findings reveal that the community-based early warning system in East Lombok still faces governance fragmentation, particularly in inter-actor coordination, role distribution, risk information integration, and the sustainability of warning communication. The study also finds that community social capacity, including trust in local actors, disaster knowledge, volunteer networks, community leadership, and the ability to undertake early action, serves as a crucial foundation for the effectiveness of early warning systems. The main contribution of this study is the formulation of a collaborative governance model consisting of five components: a multi-actor collaboration forum, clear role distribution, risk information integration, strengthening of community social capacity, and continuous evaluation. This model positions the early warning system as a socio-technical ecosystem that connects institutional capacity, warning technology, and community preparedness.